ANALISIS KEMAMPUAN MAHASISWA CALON GURU FISIKA DALAM MENGINTERPRETASIKAN DAN MENGGUNAKAN KURIKULUM MERDEKA - Lutfin, Nursakinah Annisa; Rahmadhani, Aulia; Tuada, Rasydah Nur (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to get an overview of the abilities of prospective physics teacher students in interpreting and using the Independent Curriculum. The sample for this study was 55 physics education study program students from the 2019-2021 class at the University of West Sulawesi, who were selected based on the experience of students teaching at school and who had programmed microteaching and PPL courses. The instrument used in this study was an Independent Curriculum questionnaire with alternative answers Strongly Agree (SA), Agree (A), Disagree (D), and Strongly Disagree (SD) which were compiled by researchers and validated by 3 experts. The research data were analyzed descriptively quantitatively and grouped into Very High, High, Low, and Very Low assessment criteria. The results show that the ability of prospective physics teacher students in interpreting and using the Independent Curriculum is based on indicators of understanding the outlines of the Independent Curriculum, indicators of understanding learning and assessment, indicators of understanding the development of the operational curriculum of educational units in the Independent Curriculum, and indicators of understanding the development of projects to strengthen Pancasila student profiles respectively each is in the high criteria.